Khudozhestvennyi obraz kak instrument razvitiia kommunikativnoi kul'tury vypusknikov gumanitarnogo vuza - Potanina L. T. (Socio-Pedagogical Issues of Education and Upbringing, 2022)
the importance of the artistic image in the activity of a teacher as a tool for the development of the communicative culture of a university graduate is considered. This task is implemented through the disciplines of the socio-humanitarian cycle, in particular, psychology and foreign languages. The types and functions of the language of the artistic image are discussed. The essential characteristics of the concept of "the language of an artistic image" in the context of pedagogical activity are revealed, its developing potential is indicated. Methodological tools and techniques for improving the communicative culture of graduates of a humanitarian university are proposed. The results of an empirical study on the development of the language of the artistic image among graduates of humanitarian universities are presented.
Keywords: развивающий потенциал; коммуникативная деятельность; художественный образ; коммуникативная культура; artistic image; communicative culture; язык педагога; developing potential; communicative activity; teacher's language